Sustainable Livelihood Community Level Assessment of Wayanad, Kerala - ALLISON PLATT (TUFTS UNIVERSITY, 2016)
This needs and capacity building assessment examined environmental, economic, and social conditions at a community level in Wayanad, Kerala, India, to document community-iden-tified challenges, existing assets, as well as unmet needs. Sustainable livelihood security at the household level was assessed using purposeful sampling of select vulnerable groups prioritizing women, tribals and agricultural workers through surveys and focus groups. Interviews with seven local non-profit leaders further document existing services and programs within the community. Wayanad faces challenges including land use change, a lack of waste management, gender in-equality, and unfavorable market conditions, particularly for farmers. The district has an existing network of capable organizations dedicated to sustainable living that are well connected to government planning and funding. Demand for increased services and programs can expand on the existing capacity within the community to address Wayanad’s challenges. Additional focus on program goals aimed to increase dignity and empowerment are recommended.